3-BOYUTLU UZAYDA KATI CİSİMLER ARASINDAKİ TEMAS KOORDİNATLARI - KUMARGAL, AYŞE (Fırat Üniveristesi, 2018)
Bu çalışma dört bölüm olarak düzenlenmiştir. Birinci bölümde; Giriş kısmı verildi. İkinci bölümde; Lie operatörü, Atlas, Gauss eğriliği gibi temel tanımlar verildi. Üçüncü bölümde; çalışmanın giriş kısmı verildi ve bir küre ile düzlemsel yüzeyin geometrik özellikleri incelendi. Dördüncü bölümde; Bir hareketin kapalı döngü denklemleri, hız ve ivme analizi ifade edildi. Örnekler verildi. İki kürenin birbirine göre değme hareketi, küre ile düzlemin birbirine göre değme hareketi incelendi. Bir eksen etrafında dönme hareketinin kinematiği incelendi.

This study has been arranged in four chapters. In the first chapter; Introduction In the second chapter; the fundamental definitions as lie operator, Atlas, Gaussian curvature are given. In the third chapter; the entrance part of the work was given and the geometrical properties of a sphere and the planar surface were investigated. In the fourth chapter; Closed-loop equations of a motion, velocity and acceleration analysis were expressed. Examples given. The movement of two relative to each other, the movement of the sphere to the plane relative to each other has been studied. The kinematics of the rotation about an axis have been studied.
Contact coordinates between three-dimensional rigid bodies
Keywords: Matematik